(SMAXAPR]PXAV XLV APASXYQLAMFV DN]VVLMFV ELAXAUA[FV ASR XJ KF]ULA VXJP SUAQJs - Bishop Dorothy V. M.; Norbury Courtenay Frazier; Tomblin J. Bruce (Gutenberg, 2013)
(SKFOAXA RURNRDLAV KFOAXA AQLRNRDJVJV V[FXLMA OF XJP APASXYQLAMJ DN]VVLMJ ELAXAUA[J J BUA[Y[URPJ OPJOJ VXA SALELA OF APASXYQLAMJ DN]VVLMJ ELAXAUA[Js